McCarthy score and academic performance among primary school children in Kuala Lumpur, Malaysia - Zailina Hashim; Shamsul Bahari Shamsudin; Josephine Y.; Ariffin O (2002)
The objective of this study was to determine the relationship between scores on McCarthy Scales of Children’s Abilities (MSCA) and academic performance of school children. A total of 112 first and second graders aged 6 to 8 ½ years old from two primary schools in Kuala Lumpur, Malaysia were selected as subjects for this study. This selection was based on a random sampling stratified proportionally according to school and sex. The MSCA was administered to 59 male and 53 female students. The test battery was translated from English to Malay and adapted to suit the local situation. Academic performance was measured using the mean percent of the total score on all the subjects (English, Malay, Mathematics and Islamic Religion) in the final examinations at the end of the year. T-test results indicated no significant difference between MSCA scores and academic scores of male and female students. The results revealed that all the scores on the MSCA and the General Cognitive index were significantly correlated with academic performance. The findings appear to support that intelligence scores may be used to predict children’s academic performance in the early years of primary education.